Veli-Matti Kärkkäinen"s ecclesiology and its relevance to South Africa - Miti, Bambo (HTS teologiese studies, 2020)
The South African context has been characterised by the prevalence of various social realities and problems in the form of xenophobia, racism, poverty and social injustice, aspects that adversely affect the ecumenical dream of equality, unity, love and tolerance. This article delves into these issues critically by examining how Veli-Matti Kärkkäinen’s concepts, ideas and symbols as expressed in his Pentecostal ecumenical ecclesiology can effectively inform the South African context. This article also brings into perspective the credible foundational precepts within the Pentecostal tradition that are intricately intertwined within Kärkkäinen’s ecclesiology and determines how these invaluable traits or precepts can be applied effectively within the South African context. Although these Pentecostal foundational precepts have for a long time been overlooked by traditional theologies, they are also embedded within ecumenical values such as cultural diversity, interracial communion, promotion of peace, gender equality and religious pluralism.Contribution: This article is pushing the boundaries of how Pentecostal theology in general is understood by presenting its role and function in a wider ecumenical and geographical context. In this regard, this study makes a contribution by exploring ideas from Kärkkäinen’s ecclesiology which can effectively inform the current South African context which has been plagued by elements of inequality and injustice.